Caregiver burden and healthcare providers perspectives in epilepsy: An observational study in China, Taiwan, and Argentina - Ioannis Karakis; Santiago Flesler; Sanman Ghorpade; Rio Carla Pineda; Kalpesh Joshi; James Cooper; Shilpa Patkar; Andrea Schulz; Savita Bakhshi Anand; Nicola Barnes (Epilepsy & Behavior Reports)
Caregivers are important stakeholders in epilepsy management, and effective communication between healthcare providers (HCPs) and caregivers is needed to optimize patient well-being. The study aimed to identify and evaluate the burden of epilepsy care across the age spectrum from the caregiver’s perspective and understand the perception and management of caregiver burden, including drivers of decision-making in clinical practice, by HCPs. This was a cross-sectional survey of unpaid caregivers of persons with epilepsy (PWE) and HCPs treating PWE. A total of 200 caregivers (China and Taiwan: n = 65/200, 32.5 % each; Argentina: n = 70/200, 35.0 %), and 200 HCPs (China and Taiwan: n = 70/200, 35.0 % each; Argentina: n = 60/200, 30.0 %) participated. Caregivers commonly experienced emotional impacts including anxiety (58.5 %), depression (45.5 %), work/school productivity loss (40.0 %), reduced working hours (40.0 %), or financial stress (24.5 %). HCPs identified several challenges faced by caregivers care, such as fatigue (85.0 %), poor-quality sleep (68.0 %), emotional impacts and stress (61.5 % each), anxiety (57.0 %), and worry about the patient’s future prospects (54.0 %) (e.g., health status (56.5 %), loss of work productivity/career opportunities (50.5 %), worsening of the condition (47.0 %), seizure frequency (46.0 %), and impact on quality of life (46.0 %)). Caregivers for PWE reported emotional, work-related, physical, financial, and social impacts. HCPs recognized similar findings and alignment with the caregiving burden. This study identifies gaps in caregiver support and can be a basis for future initiatives to improve the needs of caregivers and gaps in family-HCP communication so that they can partner with HCPs in the care of PWE.